Parasitism by Microctonus aethiopoides on a novel host Listronotus bonariensis in Canterbury pastures - McNeill, M.R.; Kean, J.M.; Goldson, S.L. (New Zealand Plant Protection, 2002)
The parasitoids Microctonus aethiopoides and M hyperodae have been introduced as biological control agents against Sitona discoideus and Argentine stem weevil Listronotus bonariensis respectively Collections from ryegrass/white clover pastures in midCanterbury found that M aethiopoides was widespread in L bonariensis despite the weevil being a novel host Microctonus aethiopoides was recovered from 83 of the 65 sites sampled in Canterbury with parasitism rates of 0419 Studies in lucerne crops showed that M aethiopoides preferentially parasitised its natural host S discoideus although in some cases up to 10 of L bonariensis found in the lucerne were parasitised A possible reason for the prevalence of M aethiopoides in Canterbury pasture was that the widelydispersive flights of S discoideus from aestivation sites provided a source for reinfection of the parasitoid into ryegrass pasture Analysis of field parasitism suggested that parasitism of L bonariensis by M aethiopoides was negatively correlated with parasitism by M hyperodae